Biomechanical analysis of three popular tibial designs for TAR with different implant-bone interfacial conditions and bone qualities: A finite element study. (June 2022) - Jyoti,; Mondal, Subrata; Ghosh, Rajesh
Highlights: Biomechanical performance of three popular tibial designs for TAR was evaluated. For low bone quality and low friction performance of STAR design is poor. Bone quality and implant design affect tibia bone stress. In terms of stress shielding Mobility design performed better. Abstract: Background: The long-term success of total ankle replacement (TAR) depends on both bone ingrowth and remodelling. The extreme values of implant-bone micromotion hinder bone ingrowth. Whereas, bone resorption due to bone remodelling is triggered by stress shielding. This study aims to investigate the biomechanical performance of three popular tibial designs (STAR, Salto and Mobility) for TAR with different implant-bone interfacial conditions and bone qualities. Methods: In this study, CT data were used for the geometric modelling of bone. The cancellous bone was considered to be heterogeneous with location-based properties. Total 48 Finite Element (FE) models were prepared i.e., 45 implanted and 3 intact. For the three designs, three bone qualities were considered. For each bone quality, five implant-bone interface coefficients of friction were considered (0.1 to 0.5). The proximal part of the tibia was fully constrained and dorsiflexion loading condition was applied. Results: There was a reduction in micromotion as the coefficient of friction increased and increase in micromotion as the bone quality reduced. The effect of implant-bone coefficient of friction was trivial on tibial stress (von Mises stress) however, bone quality and implant design was considerable. Stress shielding was seen in all the models and it increased when the bone quality degraded. Conclusions: This study establishes the effect of the implant-bone interfacial condition, bone quality and implant design on implant-bone micromotion and bone stress. For long-term fixation of the tibial component, due attention should be given while selecting the tibial component design for TAR, especially for STAR and Mobility design.